Information products and services of the university library: Spanish experience - Politova Olena; Hryhorevska Olena (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The purpose of the article is to analyse the peculiarities of information products and services of the library of Jaime I University in Castellуn de la Plana (Spain)as an experience that can be implemented in university libraries of Ukraine. There search methodology is based on the methods of analysis and synthesis, content analysis of open access information resources, systematisation and generalisation. The scientific novelty of the article lies in the analysis of the quality of information and educational content posted on the website of the Library of the Jaime I University in Castellуn de la Plana (Spain), dissemination of information aboutits digital resources as an accumulation of experience in creating library products and providing high-quality services to users. In the Ukrainian library science, the activity of the Jaime I University Library in creating a service-oriented electronic information space for educational and research work is considered for the firsttime. Conclusions. The study of the world experience of libraries is one of the most relevant areas of library science research. In the activities of the library of the University of Jaime I, we observe the presence of all components that provide for the successful integration of the academic library into the digital information space, especially digital services, including the creation and access to own and partner digital collections, the development of digital communication, the creation of digital content, activities on scientific and methodological support of research, student and teaching staff. The library offers its users a variety of tools for the development of research, education and self-education, which contributes to improving the quality of research support, quality of learning and teaching. One of the positive features of the library’s activities is the organisation of access to external means and open interdisciplinary information resources of other institutions. In our opinion, the principles and quality of organisation of services, information resources and tools for educational and scientific research at the Library of Jaime I University in Castellуn de la Plana (Spain) can serve as a universal model for implementation in the activities of other European libraries, including Ukrainian ones.